2019
DOI: 10.1164/rccm.201807-1287oc
|View full text |Cite
|
Sign up to set email alerts
|

Wood Smoke Exposure Alters Human Inflammatory Responses to Viral Infection in a Sex-Specific Manner. A Randomized, Placebo-controlled Study

Abstract: Rationale: Exposure to particulates from burning biomass is an increasing global health issue. Burning biomass, including wood smoke, is associated with increased lower respiratory infections.Objectives: To determine whether acute exposure to wood smoke modifies nasal inflammatory responses to influenza.Methods: Healthy young adults (n = 39) were randomized to a 2-hour controlled chamber exposure to wood smoke, where exposure levels were controlled to particulate number (wood smoke particles [WSP]; 500 mg/cm 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 53 publications
(92 reference statements)
8
53
0
Order By: Relevance
“…In contrast to the work presented here, prior studies have not specifically examined the effect of sex on cytokine release in acute or chronic e‐cig exposure. However, the studies on sex‐dependent effects of exposure to air pollution in humans (altered inflammatory response to viral infection) and the release of inflammatory mediators following LPS and bleomycin induced injury in vivo support our findings. Our results indicate that compared to females, males show increased pro‐inflammatory cytokine release following acute e‐cig exposure.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast to the work presented here, prior studies have not specifically examined the effect of sex on cytokine release in acute or chronic e‐cig exposure. However, the studies on sex‐dependent effects of exposure to air pollution in humans (altered inflammatory response to viral infection) and the release of inflammatory mediators following LPS and bleomycin induced injury in vivo support our findings. Our results indicate that compared to females, males show increased pro‐inflammatory cytokine release following acute e‐cig exposure.…”
Section: Discussionsupporting
confidence: 83%
“…were clinically signi cant decreases, it suggests asthma as a risk factor for long-term complications and not just in the context of a short-term trigger. In addition, while a differential effect between sexes was observed in the Seeley cohort and other studies have found sex difference following biomass smoke exposures (40), understanding the mechanism and signi cance is beyond the scope of the present work.…”
Section: Discussionmentioning
confidence: 73%
“…A 2019 study by Rebuli and colleagues of healthy adults (n = 39) aged between 18 and 40 years examined whether acute exposure to wood smoke particles modified nasal inflammatory responses to influenza. 7 The investigators found with aggregated data that there was no detectable change in the expression of pro-inflammatory cytokines after wood smoke exposure in contrast to the earlier in vitro study. 6 However, when the investigators de-aggregated the data with respect to the sex of the participants, they reported that in males, 13 genes, most of which were pro-inflammatory, were upregulated by wood smoke particles more than twofold in males compared to females.…”
mentioning
confidence: 83%